O-109 A first dose-response trial investigating the effects of adding choriogonadotropin beta to follitropin delta in women undergoing ovarian stimulation in a long GnRH agonist protocol. (6th August 2021) - Fernandez Sanchez, M; Višnová, H; Blockeel, C; Pinborg, A; Khalaf, Y; Larsson, P; Mannaerts, B
Abstract: Study question: Does addition of choriogonadotropin beta (CG beta) to follitropin delta increase the number of good-quality blastocysts following ovarian stimulation in a long GnRH agonist protocol? Summary answer: At the doses investigated, the addition of CG beta reduced the number of intermediate follicles and decreased the number of oocytes and blastocysts. What is known already: CG beta is a new recombinant hCG (rhCG) molecule expressed by a human cell line (PER.C6 â ) with a different glycosylation profile compared to urinary hCG or rhCG derived from a Chinese Hamster Ovary (CHO) cell-line. In the first-in-human trial, the CG beta pharmacokinetics were similar between men and women. In women, the area under the curve (AUC) and the peak serum concentration (Cmax ) increased dose proportionally following single and multiple daily doses. In men, a single dose of CG beta provided higher exposure with a longer half-life and proportionately higher testosterone production than rhCG derived from a CHO cell line. Study design, size, duration: Placebo-controlled, double-blind, randomised trial (RAINBOW) to explore the efficacy and safety of CG beta as add-on treatment to follitropin delta in women undergoing COS in a long GnRH agonist protocol. The primary endpoint was the number of good-quality blastocysts (grade 3 BB or higher, Gardner and Schoolcraft, 1999). Subjects were randomised to receive either placebo or 1, 2, 4, 8, or 12 µg CG beta added to the daily individualised follitropin delta dose during COS. Participants/materials, setting, methods: In total 619 women (30-42 years) with AMH levels between 5 and 35 pmol/L were randomized in equal proportions to the six treatment groups. All subjects were treated with an individualised dose of follitropin delta determined based on AMH (Elecsys AMH Plus Immunoassay) and body weight. Triggering was performed when 3 follicles were ≥17 mm but no more than 25 follicles ≥12 mm were reached Main results and the role of chance: The incidence of cycle cancellation (range 0%-2.9%), total follitropin delta dose (mean 112 µg) and duration of stimulation (mean 10 days) were similar across the groups. A reduced number of intermediate follicles (12 to 17 mm) and fewer oocytes (mean range 9.7 to 11.2) were observed for all doses of CG beta compared to the follitropin delta only group (mean 12.5). The mean number of goodquality blastocysts was 3.3 in the follitropin delta group and ranged between 2.1 and 3.0 across the CG beta groups. The incidence of transfer cancellation was higher in the 4, 8 and 12 µg group, mostly as no blastocyst was available for transfer. In the group receiving only follitropin delta, the ongoing pregnancy rate (10-11 weeks after transfer) was high i.e. 43% per started cycle vs 28-39% in CG beta groups and 49% per transfer vs 38-50% in the CG beta groups. In line with the number of collected oocytes, the OHSS incidence was overall lower following follitropin delta with CG beta than following follitropin delta only treatment. Regardless of the dose, CG beta was safe and well-tolerated with low risk of immunogenicity. Limitations, reasons for caution: The effect of the unique glycosylation of CG beta and the associated potency implications in women were not known prior to this trial. Further studies will be needed to evaluate potentially lower doses of CG beta for this and/or different indications. Wider implications of the findings: The high ongoing pregnancy rate in the follitropin delta group supports the use of individualised follitropin delta dosing in a long GnRH agonist protocol. The differential potency of CG beta may have impaired the growth of intermediate follicles with the investigated doses without affecting the ongoing pregnancy rates per transfer. Trial registration number: NCT03564509